2020
DOI: 10.1111/odi.13567
|View full text |Cite
|
Sign up to set email alerts
|

CTP‐CM enhances osteogenic differentiation of hPDLSCs via NF‐κB pathway

Abstract: Objective The conditioned medium of calcined tooth powder (CTP‐CM) is a type of biomimetic mineralized material and well contributing to bone healing and bone formation in vivo. However, little is known about the effect of CTP‐CM on human periodontal ligament stem cells (hPDLSCs) as well as the underlying mechanisms. Methods ALP activity assay was conducted to select the concentration with the highest ALP level, which was used for the following experiments. Cell proliferation was measured by cell counting kit‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…PDLSCs ate more iDPSC-EV than DPSC-EV, indicating increased mineralization potential, consistent with the prior finding that EVs from MSCs favor PDLSCs for regeneration [41,42]. We chose to observe the third and seventh days of inducement to illustrate a dynamic detin and bone formation process [33,34].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…PDLSCs ate more iDPSC-EV than DPSC-EV, indicating increased mineralization potential, consistent with the prior finding that EVs from MSCs favor PDLSCs for regeneration [41,42]. We chose to observe the third and seventh days of inducement to illustrate a dynamic detin and bone formation process [33,34].…”
Section: Discussionsupporting
confidence: 66%
“…The groups were marked as D0, D3 with DPSC-EV, D3 with iDPSC-EV, D7 with DPSC-EV, and D7 with iDPSC-EV. The evaluation was done by time and intergroup contrast at the same time point [33,34].…”
Section: Evs Treatmentmentioning
confidence: 99%
“…Our findings indicated that butyrate-a major subgingival bacterial metabolite-exhibited an important inhibitory effect on PDLSC osteogenic differentiation and periodontal tissue regeneration. It has been confirmed that many signalling pathways, such as the Smad, MAPK, and NF-κB pathways, are related to MSC osteogenic differentiation [31][32][33]. Here, we only explored the effect of NaB on the Smad pathway.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB signaling pathway is an important regulator of cellular gene transcription and can regulate differentiation [55]. When cells are induced by in ammatory complement, oxidative stress and other factors, leading to NF-κB pathway activation [56]. The activation of NF-κB pathway is characterized by the phosphorylation of P65 and IκBα in the cytoplasm, the translocation of P65 into the nucleus [57].…”
Section: Discussionmentioning
confidence: 99%